Teaching load assignment system for undergraduate courses in faculty of computing - 604590 Nurul Afiqah Afandi,1992- author; Siti Zaiton Mohd. Hashim, supervisor; Fakulti Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2015